A Potential Iterative Approach to 1, 4‐Dihydro‐N‐Heteroacene Arrays. Issue 3 (25th August 2021) - Plater, M. John; Harrison, William T. A.
Abstract: A new method for the synthesis of substituted 1, 4‐dihydrophenazines is reported and the structure of N ‐butyl‐5‐methyl‐3‐nitro‐5, 10‐dihydrophenazine is proven by an X‐ray single‐crystal structure determination. Abstract : N‐Butyl‐5‐methyl‐3‐nitro‐5, 10‐dihydrophenazine has been prepared and its solid‐state structure was characterised by an X‐Ray single crystal structure determination. Its potential use for an iterative synthesis of 1, 4‐dihydro‐N‐heteroacenes is discussed. A rationale for the successful synthesis of 5‐methyl‐2, 3‐dinitro‐5, 10‐dihydrophenazine from two available precursors, its thermal instability in CH2 Cl2 and its photochemical rearrangement to 10‐methyl‐3‐nitrophenazin‐2‐(10 H )‐one are discussed.